The effect of plant growth-promoting rhizobacteria on the growth, physiology, and Cd uptake of Arundo donax L. Issue 4 (3rd April 2017) - Sarathambal, Chinnathambi; Khankhane, Premraj Jagoji; Gharde, Yogita; Kumar, Bhumesh; Varun, Mayank; Arun, Sellappan
ABSTRACT: In this study, plant growth-promoting potential isolates from rhizosphere of 10 weed species grown in heavy metal-contaminated areas were identified and their effect on growth, antioxidant enzymes, and cadmium (Cd) uptake in Arundo donax L. was explored. Plant growth-promoting traits of isolates were also analyzed. These isolates were found to produce siderophores and enzymes such as 1-aminocyclopropane-1-carboxylate (ACC) deaminase, and aid in solubilization of mineral nutrients and modulate plant growth and development. Based on the presence of multiple plant growth-promoting traits, isolates were selected for molecular characterization and inoculation studies. Altogether, 58 isolates were obtained and 20% of them were able to tolerate Cd up to 400 ppm. The sequence analysis of the 16S rRNA genes indicates that the isolates belong to the phylum Firmicutes. Bacillus sp. along with mycorrhizae inoculation significantly improves the growth, the activity of antioxidants enzymes, and the Cd uptake in A. donax than Bacillus alone. Highly significant correlations were observed between Cd uptake, enzymatic activities, and plant growth characteristics at 1% level of significance. The synergistic interaction effect between these organisms helps to alleviate Cd effects on soil. Heavy metal-tolerant isolate along with arbuscular mycorrhizae (AM) could be used to improve the phytoremedial potential of plants.